Idiopathic bilateral massive perirenal subcapsular effusion: The first case in the literature. Issue 3 (August 2022) - Hacibey, Ibrahim; Sahin, Yusuf; Serifoglu, Ismail; Muslumanoglu, Ahmet Yaser
Introduction: Bilateral perirenal subcapsular effusion is a rare clinical condition and is associated with several underlying etiologies. We present a 33 years old male patient with idiopathic bilateral massive subcapsular effusion. Case presentation: A 33-year-old male patient presented to our outpatient clinic with bilateral flank pain and fever for 2 weeks. Bilateral perirenal subcapsular effusion was detected in intravenous contrast-enhanced CT and dynamic MRI. Treatment: Bilateral ultrasound-guided percutaneous drainage was performed by an expert uroradiologist to reduce the parenchymal pressure, Control CT imaging after 6 weeks demonstrate that bilateral normal kidneys. Discussion: It has been reported that subcapsular and perirenal effusion is a rare clinical condition that may develop secondary to causes such as Nephrotic syndrome, Eisenmenger Syndrome, Lymphangiomatosis, and Page Kidney Disease. In our case, the clinical symptoms of the patient regressed after the whole effusion fluid was drained. No underlying pathology was found in further examinations. Therefore, we present the first case of Idiopathic Bilateral Massive Perirenal Subcapsular Effusion in the literature.